2017
DOI: 10.2166/wp.2017.054
|View full text |Cite
|
Sign up to set email alerts
|

Emerging outcomes from a cross-disciplinary doctoral programme on water resource systems

Abstract: Interdisciplinary research and education programmes in water science are intended to produce groundbreaking research, often with an emphasis on societal relevance, and prepare future water resource experts to work across disciplines. This paper explores the emerging outcomes from an ongoing doctoral programme currently in its seventh year. Within the programme, there is both cross-disciplinary and mono-disciplinary research. Three questions are explored: (i) whether cross-disciplinary research leads to more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Numerous others have highlighted the need for closer cooperation within hydrology and with other disciplines, and suggested ways forward through interdisciplinary projects, consortia, summer institutes and doctoral programmes (e.g. McDonnell et al 2007, Maidment et al 2009, Sivapalan et al 2011, Thompson et al 2011, Takeuchi et al 2013, Carr et al 2017. Dunne (1998) suggested that a slightly stronger coordination of research efforts would be beneficial to progress.…”
Section: Activities Around More Integrated Questionsmentioning
confidence: 99%
“…Numerous others have highlighted the need for closer cooperation within hydrology and with other disciplines, and suggested ways forward through interdisciplinary projects, consortia, summer institutes and doctoral programmes (e.g. McDonnell et al 2007, Maidment et al 2009, Sivapalan et al 2011, Thompson et al 2011, Takeuchi et al 2013, Carr et al 2017. Dunne (1998) suggested that a slightly stronger coordination of research efforts would be beneficial to progress.…”
Section: Activities Around More Integrated Questionsmentioning
confidence: 99%
“…Interdisciplinarity is both a consequence of the type of societally relevant research questions being addressed in the HOAL, and it also provides an opportunity to address more complex research questions than would be possible by researchers from only one discipline. Students have clearly recognised that through collaboration with others they are able to gain knowledge and understanding that enables them to delve deeper into their own research topic (see Carr et al, 2015). Additionally, they often also see immediate benefits to their collaboration in the form of a data set, which provides further motivations for continuing to work collaboratively.…”
Section: Interdisciplinary Collaborationmentioning
confidence: 99%
“…Art pieces included paintings and stone masonry, as well as flood survival kits (including sponges, sand, inflatable rubber and information material) which were handed out to the public in ment of the candidates' subsequent career path is therefore preliminary. Experience in other doctoral programmes suggests that strong interactions amongst researchers during the PhD continue to influence their later career paths (Carr et al, 2017(Carr et al, , 2018. It will be interesting to see whether such findings are also true for the WISE CDT programme.…”
Section: International Research Visitsmentioning
confidence: 94%